2022
DOI: 10.1038/s41586-021-04229-0
|View full text |Cite
|
Sign up to set email alerts
|

Global fine-scale changes in ambient NO2 during COVID-19 lockdowns

Abstract: Nitrogen dioxide (NO2) is an important contributor to air pollution and can adversely affect human health1–9. A decrease in NO2 concentrations has been reported as a result of lockdown measures to reduce the spread of COVID-1910–20. Questions remain, however, regarding the relationship of satellite-derived atmospheric column NO2 data with health-relevant ambient ground-level concentrations, and the representativeness of limited ground-based monitoring data for global assessment. Here we derive spatially resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 73 publications
4
66
1
Order By: Relevance
“… 53 , 54 Previous studies based on ground-based measurements and satellite estimates have also reported this phenomenon. 51 , 55 The lockdown had a strong and sustained impact on surface NO 2 concentrations (relative changes > 30%) until the 48th day after the Lunar New Year (P3). After P3, the impact gradually decreased in most areas (P4) due to increasing anthropogenic emissions as the epidemic was gradually controlled and cities lifted bans.…”
Section: Resultsmentioning
confidence: 99%
“… 53 , 54 Previous studies based on ground-based measurements and satellite estimates have also reported this phenomenon. 51 , 55 The lockdown had a strong and sustained impact on surface NO 2 concentrations (relative changes > 30%) until the 48th day after the Lunar New Year (P3). After P3, the impact gradually decreased in most areas (P4) due to increasing anthropogenic emissions as the epidemic was gradually controlled and cities lifted bans.…”
Section: Resultsmentioning
confidence: 99%
“…(Jaegle et al, 2018;Salmon et al, 2018). In India, bottom-up emissions inventories report sustained growth of NOx emissions (Kurokawa and Ohara, 2020;McDuffie et al, 2020) and NO2 levels observed by OMI have been increasing since 2005 (Goldberg et al, 2021;Cooper et al, 2022). The decrease in anthropogenic NOx emissions inferred by TROPOMI observations contrasts with these trends in bottom-up estimates and OMI observations.…”
Section: Emissions Inversionmentioning
confidence: 99%
“…While non-uniform changes in NO 2 within cities are interesting and have been the subject of other studies (e.g. [48]), the primary goal of our study is to reconcile differences among cities' ∆NO 2 in light of their different diesel shares.…”
Section: Discussionmentioning
confidence: 99%